Side Reactions with an Equilibrium Constraint: Detailed Mechanism of the Substitution Reaction of Tetraplatin with dGMP as a Starting Step of the Platinum(IV) Reduction Process - Šebesta, Filip; Burda, Jaroslav V (The journal of physical chemistry. B, 2017)
Two possible pathways of the substitution reaction within the reduction process of the Pt (DACH)Cl by dGMP are compared: associative reaction course and autocatalytic Basolo-Pearson mechanisms. Since two forms: single-protonated and fully deprotonated phosphate group of dGMP are present in equilibrium at neutral and mildly acidic solutions, consideration of a side reactions scheme with acido-basic equilibrium-constraint is a very important model for obtaining reliable results. The examined complexes are optimized at the B3LYP-GD3BJ/6-31G(d) level with the COSMO implicit solvation model and Klamt's radii used for cavity construction. Energy characteristics and thermodynamics for all reaction branches are determined using the B3LYP-GD3BJ/6-311++G(2df,2pd)/IEF-PCM/scaled-UAKS level with Wertz's entropy corrections. Rate constants are estimated for each individual branch according to Eyring's transition state theory (TST), averaged according to equilibrium constraint and compared with available experimental data. The determined reaction barriers of the autocatalytic pathway fairly correspond with experimental values. Furthermore, autocatalytic reaction of tetraplatin and its two analogues complexes [Pt (en)Cl and Pt (NH ) Cl ] are explored and compared with measured data in order to examined general reaction descriptors.